Assessment of the relationship between plasma fibrinogen-to-albumin ratio and slow coronary flow phenomenon in patients without obstructive coronary artery disease - Shao-bing Yang; Ying Cui; Jian-jun Hou; Hui Zhang; Xiao-yang Pei; Yong Wang (BMC Cardiovascular Disorders, 2023)
Abstract Background Prior studies have suggested that the chronic inflammatory response has an important role in the pathophysiology of slow coronary flow phenomenon (SCFP). However, data are scarce regarding the role of plasma fibrinogen-to-albumin ratio (PFAR) in patients having SCFP without obstructive coronary artery disease (CAD). In this study, we investigated the relationship between PFAR and the presence of SCFP in patients without obstructive CAD. Methods From January 2021 to January 2023, we consecutively recruited 1085 patients without obstructive CAD according to the diagnostic and exclusion criteria. In total, SCFP was diagnosed in 70 patients. A 1:2 age-matched case–control study was then conducted using comparators without SCFP. Ultimately, this study enrolled 70 patients with angiographically normal coronary arteries and SCFP, along with 140 comparators with angiographically normal coronary arteries and normal coronary flow. Plasma fibrinogen and albumin levels were measured, and the PFAR was then calculated for each patient. Results PFARs were significantly greater in the SCFP group than in the comparators with normal coronary flow (82.8 ± 15.4 vs 73.1 ± 19.5, p < 0.001). PFAR increased with increasing numbers of vessels affected by SCFP. Multivariate logistic regression analysis showed that PFAR was an independent predictor of SCFP (odds ratio: 1.818, p = 0.015). Receiver operating characteristic (ROC) curve analysis indicated that PFAR showed a better predictive value of SCFP than fibrinogen or albumin, although not significantly (p > 0.05). Conclusion PFAR is an independent predictor of SCFP in patients without obstructive CAD. PAFR could improve the predictive value of SFCP than albumin or fibrinogen alone, but not significantly.